Improving Students’ Vocabulary for Primary Students by Using Hello English and Booktract Software - Manik, Sondang; Dewi Handayani, Roma (European Exploratory Scientific Journal, 2020)
The objective of this study was to investigate the improvement of student’s achievement in vocabulary by using Hello English and Booktrackt. Hello English and Booktrack are good software to be applied in teaching vocabulary. By using Hello English and Booktrack, the teacher can help the students in watching, listening, understanding, and applying the use of language contextually. This study is conducted by using Classroom Action Research. The Subject of this study was all the students of grade 4B and 4C Sekolah Lentera Harapan Medan with the total number of the students was 46 students. The subjects were taught by using Hello English and Booktract. The quantitative data were taken from the mean of the students in writing test. It is shown from the improvement of the mean of student’s score. The mean of students’ score in Hello English in pre-test is 70.00, and posttest 86.09, the mean of students’ score in Booktract in pre-test was 70.00 and the mean of students’ score in post-test was 86.09. The analysis of quantitative data showed that the scores improve from the first test to the last test eventually. Furthermore, it was proved through the observation sheet and diary notes, which indicate there was an improvement in learning result through using Hello English and Booktract in teaching-learning process from pre-test to post test. Therefore, Hello English and Booktract could significantly improve the students’ achievement in vocabulary. It can be suggested for English students Department, to understand the Hello English and Booktract are able to improve students’ achievement in vocabulary achievement, and the English teachers, to use Hello English and Booktract in teaching vocabulary to make students more interested and enjoyable in vocabulary achievement.